PA-MSHA induces inflamed tumor microenvironment and sensitizes tumor to anti-PD-1 therapy - Min Huang; Fang He; Dan Li; Ya-Jia Xie; Ze-Bo Jiang; Ju-Min Huang; Xiao-Ping Zhao; Ali Adnan Nasim; Jun-Hui Chen; Jin-Cai Hou; Xian-Ming Fan; Elaine Lai-Han Leung; et al. (Cell Death and Disease, 2022)
Abstract A low response rate to immune checkpoint inhibitor (ICI) therapy has impeded its clinical use. As reported previously, an inflamed tumor microenvironment (TME) was directly correlated with patients’ response to immune checkpoint blockade (ICB). Thus, restoring the cytotoxic effect of immune cells in the TME is a promising way to improve the efficacy of ICB and overcome primary resistance to immunotherapy. The effect of Pseudomonas aeruginosa mannose-sensitive-hemagglutinin (PA-MSHA) in facilitating T cell activation was determined in vitro and in vivo. Subsets of immune cells were analyzed by flow cytometry. Proteomics was carried out to comprehensively analyze the discriminated cellular kinases and transcription factors. The combinational efficacy of PA-MSHA and αPD-1 therapy was studied in vivo. In this study we demonstrated that PA-MSHA, which is a clinically used immune adjuvant, effectively induced the anti-tumor immune response and suppressed the growth of non-small cell lung cancer (NSCLC) cells. PA-MSHA showed great potential to sensitize refractory “cold” tumors to immunotherapy. It effectively enhanced macrophage M1 polarization and induced T cell activation. In vivo, in combination with αPD-1, PA-MSHA suppressed tumor growth and prolonged the survival time of allograft model mice. These results indicate that PA-MSHA is a potent agent to stimulate immune cells infiltration into the TME and consequently induces inflammation in tumors. The combination of PA-MSHA with αPD-1 is a potential strategy to enhance the clinical response rate to ICI therapy.